Caricature of Professor Russell Carpenter, 1942 (Tufts Archival Research Center, 2005)
Attached note reads, "For Bud whose influence on me and on hundreds of his other students has been greater than he knows. For Bud who made me get those diagrams on paper. From his friend and admirer, Bob"